Electoral Uncertainty, Macro-Economic Environment and Corporate Investment Strategy - LOUKIL , Sahar; BEN ROMDHANE, Youssra; KAMMOUN, Souhaila (Journal of Finance & Corporate Governance, 2019)
Our study looks at the relationship between firm’s investment spending in fixed and intangible assets and electoral uncertainty around two types of national elections: presidential and parliamentary elections. We analyze investment sensitivity to electoral uncertainty from 1996 through 2017 using a sample of 1485 firms from 45 countries. We find that, regardless election type, firm’s fixed investment significantly decrease around elections. Precisely, firms hold investment spending in before elections and restart the year following year. In this case, firms adopt a wait-and-see strategy. But, in the context of corruption control the potential negative effects are reduced. We thus highlight how different types of investments respond to various electoral shocks since microeconomic processes respond to policy uncertainty based upon firm’s resource needs. We conclude that the effect of political uncertainty on business investment depend on the degree of political uncertainty and the investment to be undertaken.